2017
DOI: 10.1111/pace.13045
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autonomic Nervous Activity in the Termination of Paroxysmal Atrial Fibrillation

Abstract: Autonomic changes critically regulate termination of PAF, which is modulated by aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Multiple studies have investigated the patterns of spontaneous AF termination (Alcaraz, Rieta, & Hornero, 2008; Chiarugi, Varanini, Cantini, Conforti, & Vrouchos, 2007; Huang et al., 2017; Lin, Chang, Eatock, Galla, & Clayton, 2017; Ndrepepa et al., 2002; Nilsson, Stridh, Bollmann, & Sörnmo, 2006). However, the results have not been unanimous.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have investigated the patterns of spontaneous AF termination (Alcaraz, Rieta, & Hornero, 2008; Chiarugi, Varanini, Cantini, Conforti, & Vrouchos, 2007; Huang et al., 2017; Lin, Chang, Eatock, Galla, & Clayton, 2017; Ndrepepa et al., 2002; Nilsson, Stridh, Bollmann, & Sörnmo, 2006). However, the results have not been unanimous.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al. (2017) demonstrated that major autonomic changes in 65% of PAF terminations were caused by sympathetic activation and parasympathetic withdrawal by analyzing the normalized LF and HF. Our findings of autonomic changes in both groups only presented a significant reduction in the parasympathetic activity, which was only partly consistent with the study because we did not observe any sympathetic activation after the termination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemola et al (6) demonstrated that intact PVs are not required for the maintenance of experimental vagal AF and ganglionated plexi ablation may suppress the vagal response and prevent AF, indicating the importance of the ANS in the pathogenesis of AF. Although the association between cardiac innervation of the ANS from the brain and AF induction was well established during the last century (7), a majority of recent studies have focused on the roles of the ANS in terms of the mechanism (8-13) and/or treatment of AF (7, 14-18). Many theories have been proposed to explain the roles of the cardiac autonomic nervous system (CANS) in arrhythmia initiation and progression such as “The Third Fat Pad,” (8) “Integration Center,” (19, 20) “Octopus” hypothesis, (9) “Little brain,” (10) and “Autonomic remodeling” (12); however, the roles of the CANS, including its upstream regulation during AF induction, remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%